Circulating Tumor DNA Identifies Diverse Landscape of Acquired Resistance to Anti–Epidermal Growth Factor Receptor Therapy in Metastatic Colorectal Cancer. Issue 3 (25th August 2022) - Topham, James T.; O'Callaghan, Chris J.; Feilotter, Harriet; Kennecke, Hagen F.; Lee, Young S.; Li, Weimin; Banks, Kimberly C.; Quinn, Katie; Renouf, Daniel J.; Jonker, Derek J.; Tu, Dongsheng; Chen, Eric X.; et al.
Abstract : PURPOSE: Anti–epidermal growth factor receptor (EGFR) antibodies are effective treatments for metastatic colorectal cancer. Improved understanding of acquired resistance mechanisms may facilitate circulating tumor DNA (ctDNA) monitoring, anti-EGFR rechallenge, and combinatorial strategies to delay resistance. METHODS: Patients with treatment-refractory metastatic colorectal cancer (n = 169) enrolled on the CO.26 trial had pre–anti-EGFR tissue whole-exome sequencing (WES) compared with baseline and week 8 ctDNA assessments with the GuardantOMNI assay. Acquired alterations were compared between patients with prior anti-EGFR therapy (n = 66) and those without. Anti-EGFR therapy occurred a median of 111 days before ctDNA assessment. RESULTS: ctDNA identified 12 genes with increased mutation frequency after anti-EGFR therapy, including EGFR ( P = .0007), KRAS ( P = .0017), LRP1B ( P = .0046), ZNF217 ( P = .0086), MAP2K1 ( P = .018), PIK3CG ( P = .018), BRAF ( P = .048), and NRAS ( P = .048). Acquired mutations appeared as multiple concurrent subclonal alterations, with most showing decay over time. Significant increases in copy-gain frequency were noted in 29 genes after anti-EGFR exposure, with notable alterations including EGFR ( P < .0001), SMO ( P < .0001), BRAF ( P < .0001), MET ( P = .0002), FLT3 ( P = .0002), NOTCH4 ( P = .0006), ERBB2 ( P = .004), and FGFR1 ( P = .006). Copy gains appeared stable without decay 8 weeks later. There were 13 gene fusions noted among 11 patients, all but one of which was associated with prior anti-EGFR therapy. Polyclonal resistance was common with acquisition of ≥ 10 resistance related alterations noted in 21% of patients with previous anti-EGFR therapy compared with 5% in those without ( P = .010). Although tumor mutation burden (TMB) did not differ pretreatment ( P = .63), anti-EGFR exposure increased TMB ( P = .028), whereas lack of anti-EGFR exposure resulted in declining TMB ( P = .014). CONCLUSION: Paired tissue and ctDNA sequencing identified multiple novel mutations, copy gains, and fusions associated with anti-EGFR therapy that frequently co-occur as subclonal alterations in the same patient.